ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНИҢ ҮЙРЕНИЛИЎ ТАРИЙХЫ - Қурбанов, М.Д. (FAN va JAMIYAT, 2020)
The article provides an explanation of the toponymic onomastics, oikonomic terms. The importance of studying oikonyms in linguistics, including onomastics, is depicted. Interpreted toponymy of the Turkic languages, and research of oikonomy. The works performed on this topic in the Karakalpak linguistics are widely described. Methods of linguistic research of geographical names interpreted.